In Morowali Regency, Central Sulawesi Province, A Strategy for Increasing Community Income Through Corporate Social Responsibility (CSR) - Mustainah Mustainah; Syufri; Andi Mascunra Amir; Sudirman (Journal of Public Administration and Government, 2022)
Morowali Regency is well-known in Central Sulawesi as one of the regencies rich in natural resources, particularly mining minerals like as nickel, iron ore, oil, and gas. Each action carries with it a certain amount of social responsibility. The purpose of this research is to examine how the strategy of adopting corporate social responsibility (CSR) initiatives to boost people's income in Morowali Regency. The descriptive qualitative research approach was applied. Data was gathered by observation, literature review, questionnaires, and in-depth interviews. The findings revealed that, first and foremost, economic development in the Morowali Regency has exhibited tremendous increase. Furthermore, corporations in Morowali Regency's Corporate Program Strategy Social Responsibility (CSR) has indirectly impacted the community's economy. Finally, there is still widespread popular opposition to the CSR program.